INFORMATION SYSTEM FOR MAKING PC WIRE HEADS WITH PNEUMATIC SYSTEMS IN HEADING MACHINE - Adam Huda Nugraha; Sandy Suryady (Asosiasi Dosen Muda Indonesia, 2023)
Pc wire or Prestressed concrete wire is iron thread with a round cross section and has indentations on its surface. Pc wire is widely used in the construction of buildings or buildings, railway sleepers and piles. This paper discusses the process of making pc wire heads and pneumatic systems that function as driving hammer dies in making pc wire. The aim of the research is to know the work process of making pc wire head (screw iron), calculating the pneumatic system for making pc wire head (screw iron). The data needed in the preparation of this report was obtained by collecting data, namely field studies which are direct data collection. data obtained through direct observation in the field accompanied by a field supervisor then Literature Study where literature study is data collection through literature books, journals, making pc wire heads by cutting pc wire with a diameter of 7.1 mm along 152 mm using a cutting grinder and then clamping it in a vise so that the screw iron does not shift when getting pressure from the die, the die will press the pc wire so that it is formed with a circular diameter of 13 mm and 7 mm thick. From the calculation of the density of dry air, the result is = 87.08 Pa, the result of the hydrostatic calculation is 609.78 Pa, and from the calculation of the Double Acting Cylinder, the result is 254.34 N.